Style Markers in Ion Simionescu’s Writing - Ioan Milică (Memoirs of the Scientific Sections of the Romanian Academy, 2023)
The scientific work of Ion Simionescu, one of the most important Romanian naturalists, outlines the development of natural sciences prior to the Second World War. The present paper aims at revealing some of the dominant stylistic markers to be found in Ion Simionescu’s writings, with special focus on his editorial contribution to popular science. At the same time, elements of stylistic continuity that can be established between the works of the Romanian naturalist and the works of great European scientists are highlighted.